Perlindungan Hukum Konsumen Pembeli Properti oleh Pelaku Usaha Properti dalam Pembangunan Perumahan - Nofriyaldi, Dio; Suardi , Suardi (PT Elaborium Elevasi Indonesia, 2025)
Property is an asset that anyone wants to own because property is a guarantee for the future when investing in asset ownership. In the modern era, there are many property business actors who offer property buying and selling services either as residences or as investment assets for the future. However, when purchasing this asset, we must be careful in choosing the property we want to buy, both in terms of location, building materials and the property business itself, this is because many property business actors do not carry out their responsibilities properly, such as late construction. , collapsed, and property business actors who ran away took away consumers' money and abdicated their responsibilities. This research aims to examine property business actors in the development of housing construction which must comply with the schedule promised to consumers so that the property can be occupied as well as the sanctions that can be given to property business actors if they neglect their responsibilities, and the legal protection of consumers in purchasing property if this occurs. something undesirable.